Could Sublingual Immunotherapy Affect Oral Health in Children with Asthma and/or Allergic Rhinitis Sensitized to House Dust Mite? - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; MUMCU, GONCA; ÖĞÜLÜR, İSMAİL; DİRESKENELİ, RAFİ HANER; BARIŞ, SAFA (KARGER, 2017)
Background: Sublingual immunotherapy (SLIT) has been successfully employed in IgE-mediated respiratory allergies. However, it is not known whether the modulation of immune responses in the sublingual area during SLIT has any deleterious effect on oral health. We sought to determine the oral health prospectively in children receiving SLIT for house dust mite allergy. Material and Methods: Eighteen children with allergic asthma and/or rhinitis and 31 agematched healthy controls (HC) were included in an openlabeled trial. Oral health was evaluated by scoring the decayed, missing, and filled teeth for primary (dmft) and permanent (DMFT) dentition, and the plaque and gingival indices. Moreover, cariogenic food intake and teeth-brushing habits were also noted at baseline and at 19 months. Results: The mean age of the SLIT participants was 9.5 +/- 3.1 years and that of the HC was 9.2 +/- 3.7 years. The mean duration of SLIT was 19.13 +/- 3.81 months. At baseline, the total dmft and DMFT indices were similar in the SLIT and HC groups (p > 0.05), which demonstrated poor hygiene overall. In the within-group comparisons at the examination at 19 months, the SLIT group had a lower number of carious primary teeth and a higher number of filled primary teeth compared to the count at baseline (p = 0.027 and p = 0.058, respectively). Conclusion: Our study showed no detrimental effect of SLIT on oral health during a period of 19 months of follow-up. Parents should be motivated to use dental health services to prevent new caries formation since our cohort had overall poor oral hygiene at the baseline. (C) 2017 S. Karger AG, Basel
Keywords: Asthma; Rhinitis; Allergy; House dust mite; Sublingual immunotherapy; Caries; Oral health; CARIES; BIOFILMS; PLAQUE; CELLS